KECURANGAN AKADEMIK DITINJAU DARI RELIGIUSITAS DAN JENIS KELAMIN PADA SEKOLAH MENENGAH ATAS YANG BERBASIS AGAMA - Tutik Fardiana Fitri; Andrian Pramadi (Perpustakaan Universitas Surabaya, 2018)
academic cheating is an act that violates the rules by using a variety of ways. The way is not allowed in academic tasks because it would interfere with the process of assesment. Academic cheating is a complex thing. A wide variety of factors can affect academic fraud. One of the factors that influence academic cheating is religiosity. The study aims to determine the correlation betwen religiosity and academik cheating in terms of gender in class X and XI of the SMA AL-ISLAM KRIAN period 2016-2017. The research is quantitative with accidental sampling technique of convenience sampling. 426 subjects the students of class X dan XI. There are 142 male and 284 female. Data analiyzed using Spearman correlation with SPSS ( Statisticalprogram for yhe social sciences) version 13.0. Results from this study that there is a negative correlation between academic cheating and religiosity r= -0.097 (p=0.046), and there are differences in academic cheating when viewed from the gender sig 0.000, so many factors in addition to religiosity affect academic cheating.